Pandangan Ulama terhadap Pergaulan Laki-Laki dan Perempuan dalam Masa Bhekalan di Desa Kedungsari Kecamatan Maron Kabupaten Probolinggo. - Imam Bukhori (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2015)
This research has an objective to know the phenomenon of Bhekalan tradition and the opinion of Ulama’ Kedungsari village Maron subs district Probolinggo regency to the social intercourse between male and female in Bhekalan period. This research is qualitative descriptive qualitative, by using social definition paradigm that is included to sociology paradigm. Meanwhile, the approach in this research uses phenomenon approach, because this research tries to understand and mean the social phenomenon. In acquiring data, the researcher uses three methods, those are: observation, interviewing, and documentation. The result of the research shows that the intercourse between male and female in Bhekalan period is fax and free and it become a custom in Kedungsari village. And those thing is cannot be rid of Ulama’. Ulama’ in that village is forced to be more creative in delivering their dakwah. Ulama’ from Kdungsari village should suggest that to restrict male and female intercourse in Bhekalan period until they get married.